Impact of green tea (Camellia sinensis) leaf extract in skim milk-goose egg yolk semen extender on the quality of Sapudi ram spermatozoa stored at 5°C - Ardina Sahra Miranda; Tri Wahyu Suprayogi; Budi Utomo; Suherni Susilowati; Yeni Dhamayanti (Universitas Airlangga, 2023)
Livestock production requires Sapudi rams, a breed native to Indonesia, to meet meat demand and food security. In artificial high-quality frozen semen is needed to spread Sapudi rams. To maximize the survival of spermatozoa during cryopreservation, semen should be stored in an extender. Green tea leaf extract (GTLE) and skim milk-goat egg yolk (SM-GEY) may be a good cryoprotectants due to their antioxidant properties. This study aimed to determine the effect of adding GTLE to the SM-GEY extender on the quality of Sapudi ram spermatozoa stored at 5°C. The fresh semen sample was divided into four different GTLE treatment groups, which each contained a 0.1 mL semen sample and a 25-mL extender of SM-GEY. Group T0: no GTLE added to SM-GEY; Groups T1, T2, and T3: 0.1 mL semen diluted in 25 mL SM-GEY with 0.05, 0.10, and 0.15 mg GTLE. Extended semen was then stored at 5°C, and its quality was evaluated daily for five days. The variables observed included spermatozoa motility, viability, and membrane integrity. Data were analyzed using one-way analysis of variance followed by Duncan's test using Statistical Program and Service Solution version 23. The result of this study was that adding 0.05 mg GTLE to 25 mL of SM-GEY extender significantly maintained the spermatozoa motility, viability, and plasma membrane integrity of Sapudi ram spermatozoa for three days at 5°C (p <0.05). Therefore, it could be concluded that adding 0.05 mg of GTLE to the SM-GEY extender preserved Sapudi ram spermatozoa's motility, viability, and membrane integrity for three days at 5°C.